Inborn Errors of Immunity: how to diagnose them? - Anete Sevciovic Grumach; Ekaterini Simões Goudouris (Elsevier, 2021)
Objectives: Inborn Errors of Immunity are characterized by infectious conditions and manifestations of immune dysregulation. The diversity of clinical phenotypes can make it difficult to direct the laboratory investigation. This article aims to update the investigation of immunological competence in the context of primary defects of the immune system. Source of data: Searches were carried out on Pubmed to review articles published in the last five years, in English, French or Spanish, using the terms "diagnosis" OR "investigation" AND "immunodeficiency" or "primary immunodeficiency" or "inborn errors of immunity" NOT "HIV". Recent textbook editions have also been consulted. Summary of findings: The immune system competence investigation should be started based on clinical phenotypes. Relevant data are: characterization of infectious conditions (location, recurrence, types of infectious agents, response to treatment), age during symptom onset and associated manifestations (growth impairment, allergy, autoimmunity, malignancies, fever and signs of inflammation without the identification of infection or autoimmunity) and family history. These data contribute to the selection of tests to be performed. Conclusions: The diagnostic investigation of Inborn Errors of Immunity should be guided by the clinical characterization of patients, aiming to optimize the use of complementary tests. Many diagnoses are attained only through genetic tests, which are not always available. However, the absence of a diagnosis of certainty should never delay the implementation of therapeutic measures that preserve patient life and health.